CO2 utilization in the production of biomass and biocompounds by three different microalgae. Issue 10 (22nd August 2017) - Assunção, Joana; Batista, Ana Paula; Manoel, João; da Silva, Teresa Lopes; Marques, Paula; Reis, Alberto; Gouveia, Luísa
Abstract: The atmospheric CO2 increase is considered the main cause of global warming. Microalgae are photosynthetic microorganisms that can help in CO2 mitigation and at the same time produce value‐added compounds. In this study, Scenedesmus obliquus, Chlorella vulgaris, and Chlorella protothecoides were cultivated under 0.035 (air), 5 and 10% (v/v) of CO2 concentrations in air to evaluate the performance of the microalgae in terms of kinetic growth parameters, theoretical CO2 biofixation rate, and biomass composition. Among the microalgae studied, S. obliquus presented the highest values of specific growth rate ( μ = 1.28 d −1 ), maximum productivities ( P max = 0.28 g L −1 d −1 ), and theoretical CO2 biofixation rates (0.56 g L −1 d −1 ) at 10% CO2 . The highest oil content was found at 5% CO2, and the fatty acid profile was not influenced by the concentration of CO2 in the inflow gas mixture and was in compliance with EN 14214, being suitable for biodiesel purposes. The impact of the CO2 on S. obliquus cells' viability/cell membrane integrity evaluated by the in‐line flow cytometry is quite innovative and fast, and revealed that 86.4% of the cells were damaged/permeabilized in cultures without the addition of CO2 .